Political Theory and the Displacement of Politics - Honig, Bonnie (Book collections on Project MUSE., 2023)
"This book, now in a 30th anniversary edition, has been called a founding text of agonism, which treats political contestation not as a regrettably necessary way to correct political imperfections but as a necessary, sometimes joyful feature of democratic life. By rethinking the established relation between politics and political theory, Honig argues that political theorists of opposing positions often treat political theory less as an exploration of politics than as a series of devices for its displacement"--